In situ self-assembled N-rich carbon on pristine graphene as a highly effective support and cocatalyst of short Pt nanoparticle chains for superior electrocatalytic activity toward methanol oxidation. Issue 43 (2nd November 2021) - Fan, Xiuling; Zhao, Ming; Li, Tianhao; Zhang, Lian Ying; Jing, Maoxiang; Yuan, Weiyong; Li, Chang Ming
Abstract : Pristine-graphene-supported N-rich self-assembled carbon serves as an effective support and cocatalyst of Pt nanoparticle chains for superior MOR activity. Abstract : Highly conductive cocatalysts with great promotion effects are critical for the development of pristine graphene supported Pt-based catalysts for the methanol oxidation reaction (MOR) in direct methanol fuel cells (DMFCs). However, identification of these cocatalysts and controlled fabrication of Pt/cocatalyst/graphene hybrids with superior catalytic performance present great challenges. For the first time, pristine graphene supported N-rich carbon (NC) has been controllably fabricated via ionic-liquid-based in situ self-assembly for in situ growth of small and uniformly dispersed Pt NP chains to improve the MOR catalytic activity. It is discovered that the NC serves simultaneously as a linker to facilitate in situ nucleation of Pt, a stabilizer to restrict its growth and aggregation, and a structure-directing agent to induce the formation of Pt NP chains. The obtained nanohybrid shows a much higher forward peak current density than commercial Pt/C and most reported noncovalently functionalized carbon (NFC) supported Pt catalysts, a lower onset potential than almost all commercial Pt/C and NFC supported Pt, and greatly enhanced durability compared to graphene supported Pt NPs and commercial Pt/C. The superior catalytic performance is ascribed to the uniformly dispersed, small-diameter, and short Pt NP chains supported on highly conductive G@NC providing high ECSA and improved CO tolerance and the NC with high content of graphitic N greatly enhancing the intrinsic activity and CO tolerance of Pt and offering numerous binding sites for robustly attaching Pt. This work not only identifies and controllably fabricates a novel cocatalyst to significantly promote the catalytic activity of pristine graphene supported Pt but provides a facile and economical strategy for the controlled synthesis of high-performance integrated catalysts for the MOR in DMFCs.